International Determinants of State Agencies’ Capacity: Lessons from Colombia and Peru - Dargent Bocanegra, Eduardo (2014)
The capacity of state agencies varies greatly among Latin American states, but this significant variation remains largely understudied in political science. The few studies that do analyze this phenomenon primarily concentrate on domestic causes as explanations for the variation. This article focuses on another influence on agency capacities that contributes to understand this uneven capacity of the state in the region: international determinants, and proposes two mechanisms that link external causes to enhancement of agency capacities in developing states: a) capacity by external challenges and b) capacity by external linkages. The operation of these mechanisms is illustrated through an analysis of state agencies in Colombia and Peru.